A photoelectron spectroscopy study of ion-irradiation induced defects in single-wall carbon nanotubes - Chakraborty, A.K.; Wooley, R.A.J.; Butenko, Yu. V.; Siller, L.; Hunt, M.R.C (Carbon, 2025)
Valence band and core level photoemission spectroscopies were used to study the changes brought about by irradiation of a singlewall carbon nanotube (SWCNT) film by 3 keV Ar+ ions at room temperature. At low ion doses (low defect density) an increase in spectral intensity near the Fermi level (E-F) is observed, associated with formation of localized defect-related states. These states are acceptor-like as evidenced by a shift to lower binding energy for both valence band features and the Cls core level. For large ion doses (high defect density) the spectral intensity near E-F decreases, valence band features associated with delocalized pi bonding disappear, and a core level component associated with SP3 bound carbon appears. This behaviour is attributed to amorphisation of the SWCNT films and occurs at ion doses consistent with those theoretically predicted. (C) 2007 Elsevier Ltd. All rights reserved.